Problematika dolgoročne hrambe spletnih strani - Dečman, Mitja (Knjižnica, 2011)
The World Wide Web is a distributed collection of web sites available on the Internet anywhere in the world. Its content is constantly changing: old data are being replaced which causes constant loss of a huge amount of information and consequently the loss of scientific, cultural and other heritage. Often, unnoticeably even legal certainty is questioned. In what way the data on the web can be stored and how to preserve them for the long term is a great challenge. Even though some good practices have been developed, the question of final solution on the national level still remains. The paper presents the problems of long-term preservation of web pages from technical and organizational point of view. It includes phases such as capturing and preserving web pages, focusing on good solutions, world practices and strategies to find solutions in this area developed by different countries. The paper suggests some conceptual steps that have to be defined in Slovenia which would serve as a framework for all document creators in the web environment and therefore contributes to the consciousness in this field, mitigating problems of all dealing with these issues today and in the future.
Keywords: digitalni arhivi; digitalni viri; dolgoročna hramba; trajno ohranjanje; spletne strani; zajemanje